Impacts of nutritional stress on the survival and developmental time to metamorphosis in megalopa larvae of the exploited mangrove crab, Ucides cordatus (Ucididae). Issue 8 (14th September 2018) - Souza, Adelson Silva de; Simith, Darlan de Jesus de Brito; Abrunhosa, Fernando Araújo
ABSTRACT: Temporal variation in food availability may affect the early life-history stages of many decapod crustaceans in the pelagic environment. Here, we investigated whether temporary food restrictions affect the survival and developmental period in the last larval stage (i.e. megalopa) of the mangrove crab Ucides cordatus . We further examined whether the prior nutritional history experienced during the megalopal life affects the body size (carapace width) of the first juvenile crab stage of this species. Megalopae were subjected to five different periods (1, 3, 5, 7, and 9 days) of initial starvation followed by constant feeding ('Point of No Return' experiment), or initial feeding with subsequent food deprivation ('Point of Reserve Saturation' experiment). They were also starved or fed ( Artemia sp. nauplii) constantly in two control groups. Our results showed that U. cordatus megalopae may tolerate only one day without food, but need to feed for at least three, five or seven days at the beginning of their development to avoid a significantly lower survival and/or a delay in larval metamorphosis when compared to larvae fed constantly. However, megalopae initially fed from one to seven days may produce juveniles of smaller body size than those larvae fed for nine days or constantly.